Design of a sentence identification test with pictures (TIS-F) based on the pediatric speech intelligibility test - Vellozo,Fernanda Freitas (2017)
ABSTRACT Purposes: to design a sentence identification test with pictures for adults (Teste de Identificação de Sentenças com Figuras (TIS-F)) as an alternative for evaluation of auditory figure-background ability for verbal sounds, based on the Pediatric Speech Intelligibility Test and also for assessment of unskillful individuals who cannot accomplish other tests with higher levels of difficulty and greater demands. Methods: the Adobe Illustrator software was used and the image vectorization technique applied for figures creation. The sentences and the competitive message were audio-recorded in a sound treated room by a female announcer, using the software - REAPER - FM Digital Audio Workstation. Results: the TIS-F consisted of a 32 x 45 cm card, containing 10 figures, each one measuring 12 x 12 cm; one compact disc containing a track with the test calibration tone and seven test tracks, each one containing ten sentences and a competitive message and a specific protocol. Conclusion: the TIS-F is composed of a compact disc with dual-channel recording, with seven tracks containing ten sentences and the competitive story, one card containing ten pictures and a labeling protocol for all presentations and S/N in use, as well as the established normality values.